Mister exam

# 5x(x-4)-x(3+5x)=4 equation

A equation with variable:

#### Numerical solution:

Do search numerical solution at
[, ]

### The solution

You have entered [src]
5*x*(x - 4) - x*(3 + 5*x) = 4
$$- x \left(5 x + 3\right) + 5 x \left(x - 4\right) = 4$$
Detail solution
Given the linear equation:
5*x*(x-4)-x*(3+5*x) = 4

Expand brackets in the left part
5*xx-4-x3+5*x = 4

Looking for similar summands in the left part:
-x*(3 + 5*x) + 5*x*(-4 + x) = 4

Move free summands (without x)
from left part to right part, we given:
$$5 x \left(x - 4\right) - x \left(5 x + 3\right) + 4 = 8$$
Divide both parts of the equation by (4 - x*(3 + 5*x) + 5*x*(-4 + x))/x
x = 8 / ((4 - x*(3 + 5*x) + 5*x*(-4 + x))/x)

We get the answer: x = -4/23
The graph
Rapid solution [src]
x1 = -4/23
$$x_{1} = - \frac{4}{23}$$
x1 = -4/23
Sum and product of roots [src]
sum
-4/23
$$- \frac{4}{23}$$
=
-4/23
$$- \frac{4}{23}$$
product
-4/23
$$- \frac{4}{23}$$
=
-4/23
$$- \frac{4}{23}$$
-4/23
x1 = -0.173913043478261
x1 = -0.173913043478261
To see a detailed solution - share to all your student friends
To see a detailed solution,
share to all your student friends: